Radiation Emergency Medical Preparedness in Japan: A Survey of Nuclear Emergency Core Hospitals. (7th February 2023) - Nagata, Takashi; Arishima, Takuro; Yamaguchi, Yoshihiro; Hirohashi, Nobuyuki; Usa, Toshiro; Hasegawa, Arifumi; Hanada, Hiroyuki; Yamamoto, Naoyuki; Okamoto, Tadashi; Akahoshi, Tomohiko; Hamada, Masahiko; Abe, Takeru; et al.
Abstract: Objective: Based on experiences following the Great East Japan Earthquake and nuclear power plant accident in 2011, Nuclear Emergency Core Hospitals (NECHs) were designated as centers for radiation disaster management in Japan. This study aimed to investigate their current status and identify areas for improvement. Methods: This cross-sectional study was conducted in October 2018. Demographic data were collected by a questionnaire with free text responses about attitudes toward NECHs. Considerations regarding risk communications during a radiation disaster were analyzed using qualitative text mining analysis. Results: A total of 36 hospitals participated in this study. Only 31% of NECHs anticipated a radiation disaster. The importance of business continuity plans and risk communications was shown. Text analysis identified 7 important categories for health care workers during a radiation disaster, including media response, communications to hospital staff, risk communications, radiation effects on children, planning for a radiation disaster in the region, rumors, and the role in the region. Conclusion: The radiation disaster medical system and NECHs in Japan were surveyed. The importance of risk communications, planning for a radiation disaster in each region, and the role in the region are identified as issues that need to be addressed.